Efficiency assessment for antihypertensive, hemodynamic, renal effects of adenosine-converting enzyme (ACE) inhibitors and irbesartan and impact on endothelial disfunction in patients with stage II hypertension - M. V. Pereviazkina (Zaporožskij Medicinskij Žurnal)
Aim. To provide a comparative assessment of the impact of enalapril maleate and Irbesartanum on renal function, endothelium, hemodynamic and blood pressure in patients with essential hypertension stage II.